Distribution of Verbs Prefixed N- in Bahasa on Indonesian Language Textbooks for VII Grade (2014 & 2017 Editions) - Najiibah Najiibah; Ngaestyono Prayoga; Vargheese K J (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is conducted to determine the various categories of word classes forming inflectional and derivational verbs. This study also aims to determine the productivity of inflectional and derivational verbs with the distribution of verbs with prefix N-. The research was conducted using a descriptive qualitative method based on the existing Indonesian Textbooks for VII Grade. The instrument in this study uses techniques and models in the analysis of morphological units in morphological studies. The data collection technique was used with free listening, speaking, and note-taking techniques. Data analysis was carried out after the data had been collected by formulating by ordinary words which included also describing the process of processing verbs and the results of obtaining verb formations; and making formulations using signs or symbols. It was revealed that two types of verbs were found, namely inflectional verbs and derivational verbs. Inflectional verbs came from word formations categorized as verbs and there was no word categorical change. Derivational verbs came from word formations that caused categorical changes to word classes, found one the category of forming derivational verbs, and inflectional verbs are more productive than derivational verbs in the Indonesian textbooks studied.